(untitled) (Research, Society and Development, 2021)
In the southern region of Rio Grande do Sul, rice processing industries produce a large volume of waste such as husk and sludge from the parboiling rice process. These residues, which cause problems to the environment, can be promising for use as substrates in the production of forest seedlings. Based on this fact, the objective of this research was to verify the possibility of producing cedro (Cedrela fissilis Vell.) seedlings from agro-industrial waste, to consequent costs reducing, in the acquisition of commercial substrates, and minimization of environmental problems. Completely randomized experimental design, containing four replications with 20 polyethylene tubes per plot, was used, totaling 480 polyethylene tubes The treatments were: T1 - 100% commercial substrate; T2 - 100% carbonized rice husk (CAC); T3 - 100% parboiled rice sludge (LP); T4 - 50% CAC and 50% commercial substrate; T5 - 50% LP and 50% commercial substrate and T6 - 50% LP and 50% CAC. The variables analyzed were: percentage of emergence, emergence rate index, fresh weight of shoot and root, dry weight of shoot and root, shoot height, the longest root length and stem diameter. The results showed that sludge, mixed with commercial substrate, reduces production costs, providing seedlings with better growth and quality, and can be indicated for the production of cedro seedlings, constituting an environmentally correct solution for their destination.